2022
DOI: 10.1007/s41999-021-00599-w
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators in using a Clinical Decision Support System for fall risk management for older people: a European survey

Abstract: AimThe aim of our study was to assess barriers and facilitators to CDSS use reported by European physicians treating older fallers and explore differences in their perceptions. Findings Our main findings were that a barrier to CDSS use is that physicians feel that complex geriatric patients need a physician's clinical judgement and not the advice of a CDSS. Regional differences in barrier and facilitator perceptions occurred across Europe. Message Our main message is that when designing a CDSS for Geriatric fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Technical issues, having to indicate a reason for overriding an alert and unclear advice were perceived as the most important barriers, as well as time-expenditure of the CDSS, the need of integration with existing systems and accurate advice for medically complex clients. Relevant facilitators were a CDSS that is beneficial to patient care, easy-touse and easily accessible, contributed to increased work efficiency, fits into the physician's workflow and supportive to the decision-making process [52].…”
Section: Discussionmentioning
confidence: 99%
“…Technical issues, having to indicate a reason for overriding an alert and unclear advice were perceived as the most important barriers, as well as time-expenditure of the CDSS, the need of integration with existing systems and accurate advice for medically complex clients. Relevant facilitators were a CDSS that is beneficial to patient care, easy-touse and easily accessible, contributed to increased work efficiency, fits into the physician's workflow and supportive to the decision-making process [52].…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we report in detail the results of the scoping literature review, semi-structured interviews, software development, and usability testing rounds. The results of the systematic literature review, European online survey, modified Delphi study, and development of the fall-risk prediction model are reported in detail elsewhere by the research team [32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…For those countries formally lacking geriatric medicine as a specialty (Greece and Portugal), hospital-based physicians specializing in care of older patients (and their trainees) were eligible, and are further in this paper referred to as geriatricians. Based on the response rate among European physicians treating older adults in an earlier survey project [ 23 ], and the fact that this would be sufficient to perform sub analyses, we aimed to include approximately 1000 participants from as many European countries as possible. No formal power calculation was performed.…”
Section: Methodsmentioning
confidence: 99%